Pengenalan Pendidikan Bahasa Arab dan Ilmu Syar'i untuk Anak Usia Dini melalui Program Mahasiswa KKN - Nurul Ibni Sabella; Fatimah Azzahra; Putri Aulia Hakim; Kania Salma Alfiana; Gita Safitriana (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Community Service Program (KKN) is a form of student service to the community. This KKN was carried out at TPA Miftahul Jannah, Bantarjaya Village, Pebayuran District, Bekasi Regency with the theme ‘Improving Community Islamic Literacy’. Planting Islamic values from an early age is a strategic step in shaping children's character. This research aims to introduce Arabic language education and shar'i knowledge to early childhood through programs carried out by KKN students, including the introduction of Arabic language, recitation guidance, afternoon dhikr, provision of mufrodat, introduction to manners, and quiz competitions. The method used is descriptive qualitative with a participatory approach, where students are directly involved in designing and implementing contextual and fun learning activities. The results showed that the game-based educational approach was effective in introducing basic Arabic vocabulary and shar'i values, such as morals, worship, and daily manners. This study recommends the sustainable development of similar programs to support the formation of children's Islamic foundations from an early age.